New Proposed Conjugate Gradient Method for Nonlinear Unconstrained Optimization - Shareef, Salah G.; Omar, Dlovan H. (Science Journal of University of Zakho, 2016)
In this paper, we suggest a new conjugate gradient method for unconstrained optimization by using homotopy theory. Our suggestion algorithm satisfies the conjugacy and descent conditions. Numerical result shows that our new algorithm is better than the standard CG algorithm with respect to the NOI and NOF.
Keywords: Unconstrained Optimization; Conjugate Gradient Method; Homotopy Theory